Human Resource Management in the Europian Health System-A Comparative Approach - Kanellopoulos, Dimitrios (Mediterranean Journal of Social Sciences, 2012)
This paper was done to highlight the trends in human resource management in health care system .In this paper weanalyze human resources management in health system in several European countries , we also analyze the trends in HumanResources management in the health system in European Union. Based on this analysis we have built an extrapolation inEuropean level, in perspective of standardization and improvement of social systems in different European countries. This paperaims to support HRM strategies in health sector and to assist the decisions of preparation, training and specialization ofdoctors.